Prevalence, incidence and relative risk of cardiovascular disease risk factors in adults with atopic dermatitis: A systematic review - Jacob P. Thyssen; Jorge A. Ross Terres; Evangeline J. Pierce; Meghan A. Feely; Jonathan I. Silverberg (Wiley, 2023)
Abstract Atopic dermatitis (AD) has been associated with cardiovascular disease (CVD). A better understanding of CVD risk factors in AD populations may help dermatologists better counsel their patients regarding potential risks and treatment choices. This systematic literature review evaluated the prevalence, absolute risk (i.e.,  incidence) and relative risk of CVD risk factors in adults with AD. MEDLINE, Embase and The Cochrane Library were searched for English‐language articles published between January 2005 and the search date (16-17 March 2021) using terms for AD, prevalence/risk and CVD risk factors. Observational studies that reported the prevalence, absolute risk and/or relative risk of CVD risk factors in adults with AD were eligible. Of the 1277 unique articles identified, 71 met the inclusion criteria. Most studies were cross‐sectional or retrospective cohort studies from Europe, North America or Asia; many used national databases. Studies were heterogeneous, with inconsistent definitions of AD and risk factors (especially smoking and obesity), different methodologies and different populations (e.g., ethnicity). Within most controlled studies, the prevalence of several risk factors, particularly obesity, hypertension and dyslipidemia, was higher for AD than for controls. Where assessed, the prevalence of most CVD risk factors increased with increasing AD severity. Relative risks varied across studies. Only nine studies reported the temporal relationship between AD and CVD risk factors. Six studies reported absolute or relative risk of developing CVD risk factors (diabetes, hypertension and smoking) in AD populations; only one of these reported an elevated risk (hypertension). Despite the high number of studies to date, conclusive data regarding the relationship between AD and many CVD risk factors are lacking, and additional, carefully designed, prospective studies are required. Video Video content can be heard at https://onlinelibrary.wiley.com/doi/10.1002/jvc2.87